Organization and functions of genes in the upstream region of tyrT of Escherichia coli: phenotypes of mutants with partial deletion of a new gene (tgs). - Bösl, M (1994)
A delta tyrT::kan mutant from Escherichia coli K-12 (DTK-12) shows a transient growth lag that is caused by glycine starvation (U. Michelsen, M. Bösl, T. Dingermann, and H. Kersten, J. Bacteriol. 171:5987-5994, 1989). The same deletion, transduced into the relA1 spoT1 mutant CA274 to construct strain DTC274, caused complete growth inhibition in glucose minimal medium. Here, we show that the tyrT 5' region contains three new open reading frames in the order ORF37-->ORF34-->ORF32-->tyrT and that the delta tyrT::kan allele used previously deletes tyrT as well as a carboxy-terminal portion of ORF32. A plasmid encoding ORF32 totally complemented the inability of strain DTC274 to grow on glucose minimal medium as well as the transient glycine starvation phenomenon in DTK-12, and ORF32 was designated tgs. Partial deletion of tgs, cotransduced with the marker delta tyrT::kan, was responsible for the completely different phenotypes of the deletion mutants DTK-12 and DTC274. The deduced Tgs protein sequence showed significant homology to the PurN protein of E. coli and to enzymes with glycinamide ribonucleotide transformylase activity. We discuss whether growth inhibition in strain DTC274 may be caused by synergistic effects with the preexisting mutations relA1 and spoT1. The deduced protein sequence of ORF37 showed striking similarity to regulator response proteins and is probably a new member of this family. A spontaneous mutation in ORF37, caused by the integration of an insertion element, IS1, exhibited no phenotype.